Empowering Local Economies: A Comprehensive Study on Leading Products in Pemalang Regency - Setiawan, Avi Budi; Mochammad Yusuf; Syaiful Amin; Wahyu Ananda Putri (Efficient: Indonesian Journal of Development Economics, 2025)
The economic development of Pemalang Regency holds significant potential, given its abundant natural resources and cultural heritage. However, the region faces challenges in optimizing these assets to reduce inequality and foster inclusive growth. Identifying leading sectors and superior products is crucial for promoting sustainable economic transformation. This study employs Location Quotient (LQ), Shift Share (SS), Klassen Typology, and statistic descriptive analysis to assess sectoral performance and prioritize economic development strategies. Data collection involved purposive sampling across all subdistricts, ensuring representativeness and balanced insights. Findings reveal that agriculture, forestry, fisheries, and the financial sector are advanced and fast-growing, while several sectors such as transportation and warehousing are developed but under pressure. Notable products include honey pineaple, coffee, milkfish, textiles, and processed foods, which demonstrate significant growth potential when supported by targeted investments and strategic marketing. It is recommended that policymakers focus on developing infrastructure, fostering innovation, and enhancing human capital to strengthen these key sectors. Furthermore, promoting digital marketing and facilitating partnerships can expand market access and enhance competitiveness, ensuring Pemalang's economic sustainability in the long term.